Association of PER2 gene single nucleotide polymorphisms with genetic susceptibility to systemic lupus erythematosus. (April 2021) - Dan, Yi-Lin; Zhao, Chan-Na; Mao, Yan-Mei; Wu, Qian; He, Yi-Sheng; Hu, Yu-Qian; Xiang, Kun; Yang, Xiao-Ke; Sam, Napoleon Bellua; Wu, Guo-Cui; Pan, Hai-Feng
The circadian clock plays a crucial role in the progress of systemic lupus erythematosus (SLE). In this study, we performed a case-control study to explore the association between Period 2 (PER2) gene single nucleotide polymorphisms (SNPs) and the susceptibility of systemic lupus erythematosus (SLE). A total of 492 SLE patients and 493 healthy controls were included. The improved multiple ligase detection reaction (iMLDR) was used for genotyping. The correlations between four SNPs of PER2 (rs10929273, rs11894491, rs36124720, rs934945) and the genetic susceptibility and clinical manifestations of SLE were analyzed. Significant differences were observed in the distributions of allele frequencies and genotype under dominant model in rs11894491 between SLE patients and controls ( p  = 0.030, p  = 022, respectively). We hypothesized that PER2 gene SNPs was related to the genetic susceptibility and clinical manifestations, implying the potential role of PER2 in the pathogenesis of SLE.